MANAJEMEN KEUANGAN MADRASAH - Fahrurrozi Fahrurrozi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This research aims to recognize the accoutability of financial management of Madrasah Aliyah Pesantren in Semarang and the acculturation of acountable financial management to improve qualified education of Madrasah Aliyah at Pesantren Hidayatussubban in Semarang. The methods for collecting data consists of observation, and documents study. A critical analysis was used to analyze the data. Based on the method above, educational finance management of Madrasah Aliyah Pesantren Hidayatussubban in Semarang, is generally not accountable. It can be recognized from the weakness of budgetting system and the weakness of finance control, but the finance accounting of Madrasah Aliyah is sufficient enough. Therefore, to build the accountable culture of financial management, Madrasah Aliyah must establish financial management system for the development of education quality which consists of inputs, process, outputs, and objectives. To achieve this objectives, it needs some input standards, process standards, and output standards.